Digitalization of Economy and Electronic Payment System – Overcoming the Challenges for India - Pahwa, M.S; Dadhich, M; Chhabra, I (International Journal of Computer Sciences and Engineering, 2025)
One of the foremost important and flagship objective of the Government of India is Digital India. It can be seen that Government has been conducting various experiments for making Digital India, some were successful while other failed. At present it would be difficult to declare the success, however, an attempt of making India a “Cashless, Paperless and Faceless” economy, at least made the country move some step toward the goal. The present paper endeavors to throw some light on the concept of “India as a Cashless Economy” and efforts to understand the challenges of this transition phase. The research design is exploratory. An attempt has been made to relook the system of cashless payment with an objective to review how the challenges may be overcome. The data used is secondary from RBI website as well as from various online sources